Ox meat traceability: practical implementation using electronic identification and molecular markers - Egozcue J.; Lavín P.; Soret B.; Arana A. (Mediterranean livestock production: uncertainties and opportunities, 2008)
An integral control system to assure meat traceability from producers to consumers was developed. After birth, oxen are identified by a ruminal bolus electronic device (transponder) placed in the animal forestomach until slaughter. The registered transponder number identifies the animals during their whole life and after slaughter, it also identifies the carcasses and the commercial retail cuts. To guarantee meat traceability throughout the whole meat chain, a DNA-based control and verification procedure was established and its implementation evaluated. In this work the actions performed to establish the procedure to audit the traceability system are described. In order to create a bank of ox samples, an individual identification card containing the identification data and a blood sample on filter paper was elaborated. Once prepared, the card was laminated and stored at room temperature. The implementation of the control procedure consisted of a comparison between the DNA marker profiles of the meat samples collected anonymously at the butcher's or restaurant, and the DNA markers profiles of the blood on the identification card. This procedure was successfully completed.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)